Forest tenure reform: exclusion of tribal women’s rights in semi-arid Rajasthan, India - Bose, P. (2011)
The current trend in forest tenure reform promotes identity-based categories, such as indigenous people, on the assumption that this provides better access to forest resources for marginalized groups. India’s historic Forest Rights Act of 2006 recognizes the traditional rights of the scheduled tribes and other forest-dependent people dwelling in and around forestlands. This paper examines the politics of individual and collective access to forestland and the political representation of Bhil tribal women in the semi-arid Banswara district, Rajasthan, India. Data were collected through in-depth interviews with 54 informants, and two focus group discussions. A rights-based access approach was used to analyse outcomes of forest tenure reform on tribal women’s access to forestland, and inclusion in, and/or exclusion from, collective decision making about forestland management. The findings indicate that the new identity-based forest tenure reform is mere tokenism and hinders rather than promotes tribal women’s political empowerment and access to forest-based resources.